Comparative Study of Rebamipide & Betamethasone in Managing Stomatopyrosis in Oral Submucous Fibrosis (OSMF) Patients - Asdullah, Md.; Tiwari, R. K.; Verma, Pradhuman; J Khwaja, Kauser; Aggarwal, Anshul; Salati, Nasir A (International Journal Of Drug Research And Dental Science, 2021)
Background: Oral submucous fibrosis (OSF) is commonly seen in the Indian subcontinent affecting individuals of all age groups. It is a potentially malignant disorder caused almost exclusively by the use of smokeless forms of tobacco products. The malignant transformation rates vary from 3 to 19%. The standard of care (SOC) in managing OSF includes habit cessation, intralesional steroid and hyaluronidase injections, and mouth opening exercises.Objectives: To evaluate the efficacy of rebamipide to reduce the oral burning sensation associated with OSMF as compared to coventional Betamethasone intralesional injection.Materials and Methods: After providing information about the study and obtaining consent, these individuals were divided into two groups of 15 each using random sampling method. Patients in the rebamipide group (group I) were prescribed 100 mg tablets of rebamipide thrice a day for 21 days. The other 15 patients (group II) were given SOC, intralesional betamethasone injection 4 mg/mL once a week for 4 weeks. Visual analog scale (VAS) with 11 points (0–10) was used to assess burning sensation in the first visit, and change in the burning sensation was assessed after every 7th day on VAS in both the groups.Results: The improvement in the VAS score in each visit was significant (p < 0.05) in the 1st, 2nd, 3rd, and 4th visit. The VAS score between the 4th and 5th visit failed to reach a statistically significant level (p>0.05). The VAS score was significantly different between the rebamipide and betamethasone group (p > 0.05) in the third & fourth visits.Conclusion: Our results showed that rebamipide was equally efficacious if not better than the betamethasone intralesional injections.